TORAJA LANGUAGE AS MOTHER TONGUE IN ARTS, CULTURE, AND CRAFTS (SBdP) LEARNING IN ELEMENTARY SCHOOL: A LITERATURE REVIEW - Reni Lolotandung; Hakpantria Hakpantria (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study examines how Toraja, an Austronesian language spoken mainly in the Tana Toraja and Toraja Utara regencies of South Sulawesi, Indonesia, can be positioned as a mother tongue within the teaching of Seni Budaya dan Prakarya (SBdP), the Arts, Culture, and Crafts subject taught in Indonesian elementary schools. Using a qualitative descriptive literature review (library research) method, this study sought to answer three research questions: (1) how has the Toraja language been documented as a mother tongue within elementary-level learning; (2) what role can the Toraja mother tongue play within SBdP instruction specifically; and (3) what benefits, challenges, and strategies have been reported in the wider literature on mother-tongue-based and local-wisdom-based elementary education that are relevant to this integration. Thirteen scholarly sources published mainly between 2016 and 2026, together with two foundational theoretical works, were selected through searches of Google Scholar, Garuda, DOAJ, and international databases, screened for relevance to mother-tongue instruction, local-wisdom-based arts education, or Toraja language and culture in schooling, and analyzed using thematic content analysis. Five recurring themes were identified: the Toraja mother tongue as a carrier of cultural values and identity; the marginal curricular position of local languages relative to the national and foreign languages; SBdP and local-wisdom-based arts learning as a natural entry point for mother-tongue integration; the cognitive, linguistic, and socio-emotional benefits documented for mother-tongue-based instruction generally; and the structural and pedagogical challenges, particularly teachers' limited proficiency in Toraja and the scarcity of Toraja-language teaching materials, that constrain implementation. The review concludes that embedding Toraja language use within SBdP activities such as weaving, wood-carving motifs, and traditional song offers a practical and low-cost pathway for revitalizing the mother tongue in elementary classrooms, provided it is supported by teacher training, contextualized materials, and stronger institutional commitment.